Degradation Studies on Plastic Food Packaging by Using Immobilized Mycelia of Pleurotus ostreatus - Nur Hanna Mohd Sabri (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To investigate the effect of biotic degradation on plastic food packaging. To investigate the effect of abiotic degradation on plastic food packaging. To determine the combination of biotic and abiotic degradation on plastic food packaging.